Grammaticalization Cases Through the Four Linguistic shifts - Mohammad Ali Al Zahrani (JURNAL ARBITRER, 2021)
The present study aims at describing the grammaticalization phenomenon of some HA elements that, to the best of the author,s knowledge, have not been dealt with. It argues that the elements xən, ʕsəs and lissa have gradually developed from the verb xalla, the preposition phrases (PP) ʕla asa:s and ila al-sa:ʕah respectively. To achieve this, the paper speculates that these developed forms have followed the prevalently agreed upon grammaticalization chains where they have undergone desemanticization (semantic shift), decategorialization (morphosyntactic shift), cliticization (morphophonological shift) and erosion (phonetic shift). These chains exhibit the grammaticalization stages of the elements under study.